2019
DOI: 10.3390/su11226357
|View full text |Cite
|
Sign up to set email alerts
|

Electric Car Purchase Price as a Factor Determining Consumers’ Choice and their Views on Incentives in Europe

Abstract: The deployment of zero-emission vehicles has the potential to drastically reduce air pollution and greenhouse gas emissions from road transport. The purpose of this study is to provide evidence on, and quantify the factors that influence, the European market for electric and fuel cell car technologies. The paper reports the results of a stated preference survey among 1,248 car owners in France, Germany, Italy, Poland, Spain and the United Kingdom. The variables that influence powertrain choice are quantified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Low costs for BEVs alone did not ensure high EV dissemination. Nevertheless, the high price of BEVs was still a barrier [14]. Non-monetary incentives, combined with indirect policies such as high registration taxes and high fuel prices, are highly effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low costs for BEVs alone did not ensure high EV dissemination. Nevertheless, the high price of BEVs was still a barrier [14]. Non-monetary incentives, combined with indirect policies such as high registration taxes and high fuel prices, are highly effective.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the most important factor was not direct subsidies but road priority (access to high-occupancy vehicle lanes (HOVs) and bus lanes). The study by Vilchez et al [14] identified factors that influenced the EV market in Europe. They concluded that the purchase price of EVs was still a barrier.…”
Section: Introductionmentioning
confidence: 99%
“…However, we must also consider the position of [11] when the authors indicate that "more subsidies do not always involve more sales" or greater acceptance, purchase, and use of the electric vehicle. This last position is also shared in [12] and [13], studies on reducing incentives for the purchase of electric vehicles in the European Union. At a more local level, studies have also been carried out on the effect of incentives via electric vehicle subsidies in Norway and the Netherlands, where different scenarios for the subsidization of electric vehicles and their effects were analyzed [14]; in Denmark, along with the incentives for its purchase [15], some psychological factors were also added.…”
Section: Literature Reviewmentioning
confidence: 92%
“…How large a premium can vary from model to model, but it inevitably increases the first-time costs of EVs. It may be that the lifetime costs of a EV are less than those of a conventional vehicle, due to its lower operating costs, but surveys have shown that the initial purchase price of a vehicle plays an inordinate role in shaping consumer purchase decisions [26]. Short-term perspectives, therefore, trump long-term considerations.…”
Section: Intrinsic Shortcomingsmentioning
confidence: 99%